Palliative systemic therapy for women with recurrent epithelial ovarian cancer: current options - Elit, Laurie (Dove Medical Press, 2013)
OBJECTIVES: To review the available systemic treatments for women with recurrent ovarian cancer. METHODS: A literature review was conducted for recurrent ovarian cancer articles in English, including randomized trials, Phase II trials, or reviews. RESULTS: We discuss the efficacy and toxicity outcomes associated with systemic therapy for platinum-sensitive and platinum-resistant ovarian cancer. Clearly, platinum-based combination systemic therapy shows a prolonged progression-free interval compared with single-agent chemotherapy with a low toxicity profile. No clear superior management strategy exists for platinum-resistant/refractory disease. Novel targeted antiangiogenic agents (eg, bevacizumab), angiopoeitin inhibitors (eg, AMG 386), and poly ADP ribose polymerase inhibitors (eg, olaparib) are reviewed. CONCLUSION: Although combination platinum-based chemotherapy has shown benefits for women with platinum-sensitive recurrent ovarian cancer, the optimal treatment strategy for those with platinum-resistant or platinum-refractory disease is not clear. Molecular and genetic targeted therapies may provide opportunities for those women with tumor profiles that show sensitivity for specific agents.